The economic crisis - challenge or opportunity for gender equality in social policy outcomes. A comparison of Denmark, Germany and the UK - Leschke, Janine; Jepsen, Maria (Brussels, 2011)
"This new working paper aims to assess the impact of the current financial and economic crisis on gender equality in terms of labour market and welfare outcomes.